2010
DOI: 10.1007/s00464-010-1085-z
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for endorectal ultrasonography in rectal cancer staging

Abstract: ERUS was accurate in preoperative staging of rectal cancer. It was an easy-to-learn procedure for accurate tumor staging, but considerable experience was required to attain accuracy for nodal staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…In addition, endorectal US has a learning curve for beginners (22). Endorectal US is an operator-dependent examination, and accuracy is closely related to the experience level of the sonologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, endorectal US has a learning curve for beginners (22). Endorectal US is an operator-dependent examination, and accuracy is closely related to the experience level of the sonologist.…”
Section: Discussionmentioning
confidence: 99%
“…Considering endorectal US was used as a routine clinical practice instead of as research in a clinical trial, their results were potentially more representative of clinical practice. In addition, a well-recognized learning curve exists for the technique because endorectal US is heavily operator dependent (22).…”
Section: Patientsmentioning
confidence: 99%
“…Another limiting factor of ERUS is its operator-dependency. At the same time, this also means that in the hands of an experienced diagnostician it is a reliable method providing a great amount of information [ 21 , 22 ]. According to our results, the learning curve is relatively short; after 30 examinations it is possible to evaluate the depth invasion of rectal cancers with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, other studies highlight the substantial operator dependence of TRUS relative to MRI and the potential impacts on accuracy and reproducibility, especially with respect to determining nodal involvement. 28,29 Much of the evidence supporting the use of MRI in the preoperative assessment of rectal cancer was generated by the MERCURY Study Group, which found a high correlation between preoperative MRI and histopathology with respect to the extramural depth (EMD) of tumor spread. 30 Similarly, other authors have reported the high accuracy of MRI for assessing both EMD and the involvement of the mesorectal fascia.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%